La cerámica arqueológica vista por un artista: ilustraciones de Antonio Tejeda sobre los materiales de la finca El Paraíso (Quetzaltenango, Guatemala) - Ciudad Ruiz, Andrés; Iglesias Ponce de León, Mª Josefa (Revista Española de Antropología Americana, 2003)
In the final decade of his life, José Alcina Franch was interested in the relationships between language and the visual arts among the Mexica, and was aware that this exploration in that field was pioneering. Taking Alcina’s research and Mercedes Montes de Oca’s works on the linguistic aspect known as diphrasism as the point of departure, this article offers some ideas about the relationships between Nahuatl diphrasism, the visual arts, and Mesoamerican cosmovision. It is proposed here that in large measure, diphrasisms allude to complementary opposition, a fundamental idea in the cosmovision under study. Three possibilities are proposed for the interrelation of symbolic diads of visual image and diphrasistic figures, in pictographic and sculptured representations.
Keywords: Nahua diphrasisms; Mexica art Mesoamerican cosmovision